1985
DOI: 10.1016/0309-1651(85)90086-4
|View full text |Cite
|
Sign up to set email alerts
|

Taurine and human spermatozoal capacitation

Abstract: The effect of taurine at various concentrations (0.01, 0.1 and 1 mM) on the in vitro motility and fertilizing capacity of human spermatozoa was studied. Spermatozoa collected from 10 normal men were washed in BWW medium and incubated with taurine for 5 hours, the period required for spermatozoal capacitation. The percent motilities were recorded at 0 and 5 hours during capacitation preincubation with taurine. After incubation, the spermatozoa were washed with BWW medium to remove taurine before insemination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…However, mouse spermatozoa do not need the addition of taurine to exhibit their full fertilizing ability (Fraser, 1986). Although it has been reported that human spermatozoa capacitate faster in medium with taurine added (Mortimer, 1986;Chan, 1985), their fertilizing ability in vitro does not seem to be increased by taurine (Mahadevan & Trounson, 1985).…”
Section: Introductionmentioning
confidence: 95%
“…However, mouse spermatozoa do not need the addition of taurine to exhibit their full fertilizing ability (Fraser, 1986). Although it has been reported that human spermatozoa capacitate faster in medium with taurine added (Mortimer, 1986;Chan, 1985), their fertilizing ability in vitro does not seem to be increased by taurine (Mahadevan & Trounson, 1985).…”
Section: Introductionmentioning
confidence: 95%
“…In general, the ability of sperm to undergo a complete AR and fertilize zona-free hamster oocytes in response to several stimuli is related to fertility status and is depressed or even absent in infertile men or couples with unexplained infertility (Bolanos et al, 1983;Chan Kyono et al (1984) Lysophosphatidyl choline Ford e t al. (1991) Critser et al (1987) Aitken et al (1983) Alvarez et al (1988) Salonen (1986) Calcium ionophore A23187 ( dValue calculated by adding up its range score in three different arrangements from the highest to the lowest value of percentages of acrosome-reacted spermatozoa and differences of percentages of acrosome reaction and penetration indexes between treated and control groups.…”
Section: Resultsmentioning
confidence: 99%